Extraction and determination of malachite green from aquatic products based on molecularly imprinted polymers. Issue 10 (2nd July 2016) - Lin, Zhengzhong; Wang, Dan; Zhang, Hongyuan; Li, Lu; Huang, Zhiyong; Shen, Jianxiong; Lin, Yuhui
ABSTRACT: Molecularly imprinted polymers (MIPs) were synthesized using malachite green (MG) as template, and methacrylic acid/sodium methacrylate as composite monomers. The equilibrium dissociation constant and apparent maximum adsorption capacity of the MIPs reach 12.2 mg·L −1 and 3.2 mg·g −1, respectively. The MIPs demonstrate excellent recognition ability due to high-affinity sites constructed by the electrostatic interaction and hydrogen bonds between template and composite monomers. The MIPs were successfully employed for the detection of MG residue in aquatic products coupled with high-performance liquid chromatography (HPLC) with a detection limit of 0.57 μg·kg −1 .